Mild Hyperthermia Responsive Liposomes for Enhanced In Vitro and In Vivo Anticancer Efficacy of Doxorubicin against Hepatocellular Carcinoma - Muhammad Abdur Rahim; Asadullah Madni; Nayab Tahir; Nasrullah Jan; Hassan Shah; Safiullah Khan; Riaz Ullah; Ahmed Bari; Muhammad Sohaib Khan (MDPI AG, 2021)
The current study is aimed to fabricate doxorubicin (Dox) loaded mild temperature responsive liposomes (MTLs) by thin film hydration technique for enhanced in vitro and in vivo anticancer efficacy against hepatocellular carcinoma. The aforementioned Dox loaded MTLs were developed and optimized with extrusion and drug loading techniques. The optimized MTLs were in optimum size range (118.20 ± 2.81-187.13 ± 4.15 nm), colloidal stability (−13.27 ± 0.04 to −32.34 ± 0.15 mV), and enhanced entrapment of Dox (28.71 ± 2.01-79.24 ± 2.16). Furthermore, the optimized formulation (MTL1-E(AL)) embodied improved physicochemical stability deducted by Fourier transform infra-red (FTIR) spectroscopy and mild hyperthermia-based phase transition demonstrated from differential scanning calorimetry (DSC). An in vitro drug release study revealed mild hyperthermia assisted rapid in vitro Dox release from MTLs-E(AL) (T100% ≈ 1 h) by Korsmeyer-Peppas model based Fickian diffusion (n < 0.45). Likewise, an in vitro cytotoxicity study and lower IC50 values also symbolized mild hyperthermia (40.2 °C) based quick and improved cytotoxicity of MTL1-E(AL) in HepG2 and MCF-7 cells than Dox. The fluorescence microscopy also represented enhanced cellular internalization of MTL1-E(AL) at mild hyperthermia compared to the normothermia (37.2 °C). In addition, an in vivo animal study portrayed the safety, improved anticancer efficacy and healing of hepatocellular carcinoma (HCC) through MTL1-E(AL). In brief, the Dox loaded MTLs could be utilized as safe and effective therapeutic strategy against HCC.